Accumulation of heavy metals in agricultural soils of Mediterranean: Insights from Argolida basin, Peloponnese, Greece - Kelepertzis, Efstratios (Geoderma, 2014)
Excessive application of chemical products for promoting crop growth is a significant contributor for elevated concentrations of heavy metals in agricultural soils potentially threatening human health through the food chain. In this study, a series of heavy metals were quantified in 132 agricultural soils of Argolida basin, Peloponnese, Greece, with the aim to characterize their accumulation patterns. Median concentrations of Cu, Pb, Zn, Ni, Co, Mn, As, Cd, Cr and Fe were 65.23, 20.1, 72.75, 120.3, 20.6, 956.5, 7.1, 0.45, 72.3 and 27,100mg/kg respectively. Statistically significant differences for Cu, Zn, Pb and Cd content were found between agricultural and background soils in the same region. Implementation of principal component analysis and cluster analysis successfully grouped the investigated chemical elements according to their anthropogenic or natural origin. The prolonged application of large amounts of fertilizers and pesticides–fungicides has resulted to Cu, Zn, Cd, Pb and As accumulation in the agricultural fields whereas Ni, Cr, Co and Fe amounts are controlled by parent material influences. Contrary to results commonly reported in the literature that characterize Mn as a geogenic element, this metal was found to exhibit a mixed source in the study agricultural system. Geographical information system techniques were used to illustrate the spatial distribution trends of the investigated elements confirming the clear contribution of agrochemicals to soil chemistry and highlighting the citrus soils around Argos town to have received large anthropogenic inputs. The agricultural area represented by olive groves does not demonstrate significant anthropogenic soil metal enrichment indicating that accumulation phenomena are restricted to the soils cultivated for oranges and mandarins. This study is the first detailed report on metal accumulation in citrus soils from Argolida basin, and results promote the care for the environment by reducing application rates of fertilizers and pesticides–fungicides and monitoring heavy metals levels in receiving soils. Future studies should pay attention to characterize the fractionation and reactivity of metals in citrus soils by utilizing selective chemical extractions with the aim to assess the actual risks for the environment. •First report on metal accumulation in Argolida agricultural soils is presented.•Contamination sources and spatial trends of metals were examined.•Agrochemicals influence Cu, Zn, Cd, Pb, As and Mn accumulation in soils.•Parent ultramafic materials are responsible for Ni, Cr and Co enrichment.•Citrus soils have received significant anthropogenic inputs.